2011
DOI: 10.1371/journal.pone.0027817
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia Is Independently Associated with Coronary Heart Disease and Renal Dysfunction in Patients with Type 2 Diabetes Mellitus

Abstract: AimsTo investigate the relationship between hyperuricemia (HUA) and the clinical backgrounds in Japanese patients with type 2 diabetes mellitus.MethodsAfter a cross-sectional study evaluating the association of HUA with the clinical characteristics in 1,213 patients with type 2 diabetes mellitus, the estimated glomerular filtration rate (eGFR) and the incidence of diabetic macroangiopathies was investigated in a prospective observational study in 1,073 patients during a 3.5 year period. HUA was defined by seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 38 publications
2
63
0
7
Order By: Relevance
“…Hence, the variations in uric acid level may be due to gender-dependent differences in the range of uric acid. The overall prevalence of hyperuricemia is 28% which is comparable with the results obtained by a study conducted in Nigeria who reported the prevalence rate to be 25% [7] and also with a study conducted by Ito H. in Japan who reported the prevalence to be 25% (9).Hyperuricemia in diabetes mellitus II is also shown by other various studies [16,17,18].In contrast to these findings, some researchers have also shown negative association between uric acid and diabetes. Cook et al explained higher mean serum uric acid values in prediabetic patients than in recently diagnosed diabetics and lower values in diabetics.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, the variations in uric acid level may be due to gender-dependent differences in the range of uric acid. The overall prevalence of hyperuricemia is 28% which is comparable with the results obtained by a study conducted in Nigeria who reported the prevalence rate to be 25% [7] and also with a study conducted by Ito H. in Japan who reported the prevalence to be 25% (9).Hyperuricemia in diabetes mellitus II is also shown by other various studies [16,17,18].In contrast to these findings, some researchers have also shown negative association between uric acid and diabetes. Cook et al explained higher mean serum uric acid values in prediabetic patients than in recently diagnosed diabetics and lower values in diabetics.…”
Section: Discussionsupporting
confidence: 86%
“…In another study from Japan including 1213 type 2 diabetic patients, a positive independent association among HUA, coronary heart disease, and renal dysfunction was reported, supporting the hypothesis that HUA is implicated in the pathogenesis of the micro-and macrovascular diabetic complications. 69 In accordance, Tanaka et al 70 reported that HUA was correlated with increased risk of macrovascular disease in diabetic CKD patients.…”
Section: Hua Diabetes and Diabetic Nephropathymentioning
confidence: 64%
“…A relationship between hyperuricemia and various MS components (hypertension, obesity, diabetes mellitus) has been demonstrated [36][37][38][39] and serum uric acid levels seem to be clearly associated with the prevalence of MS [36] and the incidence of DM [40]. In addition, in type 2 diabetic subjects hyperuricemia is correlated with the vascular complications, such as retinopathy, cerebrovascular and coronary artery diseases, and nephropathy [41].…”
Section: Discussionmentioning
confidence: 95%